2018
DOI: 10.1057/s41599-018-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate disgust reduction in and out of school and its effects on state intrinsic motivation

Abstract: Invertebrates are used in environmental, biology, and science education. However, they can elicit disgust, which can be detrimental for motivational and learning outcomes. In addition, practical work including hands-on interaction with living invertebrates could be a viable way to reduce invertebrate disgust and strengthen state intrinsic motivation. Moreover, Big-Five personality may explain the students' reaction to the exposure with live invertebrates. Therefore, the present study tested the effects of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Wilde et al (2009) have carried out a scale adaptation study involving a 12-item scale as a short and economic version of "Intrinsic Motivation Inventory "(IMI). The four-factor model of the scales was confirmed in Germany with >1,700 secondary school students by a confirmatory factor analysis (Wüst-Ackermann et al, 2018). In the present study, this 12-item, 4-factor measurement instrument developed by Wilde et al (2009) was adapted to Turkish.…”
Section: Introductionsupporting
confidence: 62%
“…Wilde et al (2009) have carried out a scale adaptation study involving a 12-item scale as a short and economic version of "Intrinsic Motivation Inventory "(IMI). The four-factor model of the scales was confirmed in Germany with >1,700 secondary school students by a confirmatory factor analysis (Wüst-Ackermann et al, 2018). In the present study, this 12-item, 4-factor measurement instrument developed by Wilde et al (2009) was adapted to Turkish.…”
Section: Introductionsupporting
confidence: 62%
“…The study encompassed a pre-test, the teaching intervention and a post-test ( Figure 2). As the purpose of the study was also to test which of the conditions, teacher-centered instruction, working at workstations or an out-of-school setting contributes most to the students' knowledge about and attitude towards wolves, the sample was divided into three groups, [36,37]. The teacher-centered School condition and the workshop School condition groups were from the general upper secondary school (School 1).…”
Section: Methodsmentioning
confidence: 99%
“…The results indicate that the university workshop treatment was most effective, even if it was performed by the same teacher and the instructions were identical for the school setting. According to Williams and Williams [57], students' motivation can also be improved by the change of learning environment, see also [35,36]. The difference may also be explained by the fact that the university group consisted mainly of veterinary technician school students, who expressed the most positive attitudes and the highest knowledge scores already before teaching.…”
Section: Attitudes and Knowledge After Treatmentmentioning
confidence: 99%
“…This line with Tan et al (2020) found that GIBIM increase students' attitude to attain components of science learning with real life situation. Moreover, study conducted on invertebrate animals about disgust reduction in and out of school using active method of teaching enhances attitude of learners towards learning invertebrate animals (Joseph et al, 2017;Wüst-Ackermann et al, 2018).…”
Section: Discussionmentioning
confidence: 99%